ANALYSIS OF THE READINESS FOR CHANGES IN THE FINANCIAL SYSTEM OF PUBLIC SERVICE AGENCY STATE UNIVERSITY (BLU) BECOME PTN LEGAL ENTITY (PTNBH) (STUDY AT UNIVERSITAS NEGERI SEMARANG - Herlina; Riza Firmansyah; Atta Putra Harjanto; Rudi Hartono (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Abstract. This study aims to analyze how the readiness of the financial system of UNNES was transformed into a PTN Legal Entities (PTNBH). Readiness that was studied included regulations or rules, financial information systems, and financial reporting readiness. The research method used is qualitative with a case approach. The data used in this study are secondary data and primary data from informants. The results show that in general, UNNES is ready to transform into a PTN Legal Entities (PTNBH) from the aspect of financial regulation readiness, financial information systems and financial reporting.   Abstrak. Penelitian ini bertujuan untuk menganalisis bagaimana kesiapan sistem keuangan UNNES bertransformasi menjadi PTN Badan Hukum (PTNBH). Kesiapan yang dikaji meliputi regulasi atau aturan, sistem informasi keuangan, dan kesiapan pelaporan keuangan. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan kasus. Data yang digunakan dalam penelitian ini adalah data sekunder dan data primer dari informan. Hasilnya menunjukkan bahwa secara umum UNNES siap bertransformasi menjadi PTN Badan Hukum (PTNBH) dari aspek kesiapan regulasi keuangan, sistem informasi keuangan dan pelaporan keuangan.